KEBIASAAN KONSUMSI KOPI DAN TINGKAT KECUKUPAN ZAT BESI DENGAN ANEMIA PADA REMAJA PUTRI - Ardiansyah, Miko; Muniroh, Lailatul; Maharani, Fenny Putri (Poltekkes Kemenkes Bandung, 2024)
Anemia is a nutritional deficiency problem that is prone to be experienced by adolescent girls. Anemia can be influenced by iron intake from food sources and other factors such as coffee consumption habits. The aim of this research was to analyze the relationship between coffee consumption habits and iron sufficiency levels with anemia in adolescent girls at SMAN 1 Manyar Gresik. The research method used was observational with a cross-sectional design. The total population consisted of 487 female students from grades X and XI at SMAN 1 Manyar Gresik. The sample size was 78 individuals selected using proportional random sampling technique. Data on iron sufficiency levels and coffee consumption habits were obtained from filling out the SQ-FFQ questionnaire. Respondents' anemia status data were obtained by measuring hemoglobin levels using a hemoglobinometer (easy touch). Data analysis was conducted using the Chi-square test. This study showed that 23% of respondents had anemia and the results of statistical tests indicated that there was a relationship between the time of coffee consumption (p= 0.005) and the level of iron intake (p=0.003) with anemia. The research concluded that sufficient iron intake and consumption of coffee more than 2 hours before/after meals will reduce the risk of anemia. Therefore, respondents are advised to pay attention to the timing of coffee consumption to avoid inhibiting iron absorption.